Fifteen-year mortality of patients with asthma–COPD overlap syndrome - Sorino, Claudio; Pedone, Claudio; Scichilone, Nicola (European journal of internal medicine, 2016)
The coexistence of asthma and chronic obstructive pulmonary disease (asthma–COPD overlap syndrome: ACOS) is increasingly recognized but data about its prevalence and long-term mortality are needed. Prevalence of ACOS and 15-year mortality rates were assessed in 1065 subjects aged >65years, enrolled in the SA.R.A. study, with complete clinical, lung functional and follow-up data. Physical performance, disease-related disability, and health-related quality of life (HRQL) were also evaluated. ACOS was found in 11.1% of subjects (29.4% of those previously diagnosed with COPD and 19.7% of those with asthma). ACOS was positively associated with impaired physical performance, functional ability, and HRQL. Individuals with ACOS had higher mortality rates than controls (7.17 per 100 person-years; mortality rate ratio: 1.83). After adjustment for the main confounders, the risk of all-cause mortality remained significantly increased in subjects with ACOS (HR: 1.82), COPD (HR: 2.12), and restriction (HR: 2.41), but not asthma. Long-term prognosis of ACOS was similar to COPD, and worse than asthma and healthy controls. ACOS had a significant impact on physical performance, functional ability, and HRQL. •ACOS negatively affects physical performance and health-related quality of life.•ACOS worsens disease-related disability.•Long-term mortality of ACOS is worse than asthma and similar to COPD.•After 65years, 1/3 of COPD patients and 1/5 of asthmatics might have ACOS.